Analysis of the Emotion Regulation Inventory through IRT - Ricarte,Mirela Dantas (2019)
Abstract Emotion regulation is a multiprocessual phenomenon capable of maintaining, intensifying or diminishing the emotional experience. This work investigated the psychometric properties of the Emotion Regulation Inventory for Learning Situations, using the Item Response Theory (IRT). Participants included 365 students from the 5th to the 9th grades of elementary school, with a mean age of 11.9 years (SD = 1.72), 57.5% female and 42.5% male. The results indicated problems in the instrument, such as small variability of the items and underutilized categories of response, and ways for the revision of the instrument, such as construction of more difficult items that require internal strategies, focused on the learning experience.